2021
DOI: 10.1186/s12882-021-02282-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes associated with rapid linear and non-linear patterns of chronic kidney disease progression

Abstract: Background Patients with rapidly declining renal function face the dual threat of end-stage renal disease (ESRD) and mortality prior to ESRD. What is less well characterised is whether the pattern of the renal trajectory, linear or non-linear, unmasks subgroups of rapidly progressing patients that face adverse outcomes in a differential manner. Methods An individual eGFR slope was applied to all outpatient estimated glomerular filtration rate (eGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…The Salford Kidney Study (SKS), is a longitudinal, prospectively collected, ongoing observational study with full ethical permission that has recruited and followed-up patients with non-dialysis dependent CKD (NDD-CKD) in the United Kingdom since March 2002 [ 25 , 28 ]. This large NDD-CKD cohort consists of > 3500 patients that have provided their informed consent when admitted to the nephrology inpatient centre at Salford Royal Hospital or referred to nephrology outpatient clinics [ 8 , 26 ]. The participants in the current study were ≥ 18 years at the time of consent with (eGFR) < 60 ml/min/1.73 m 2 who had not started renal replacement therapy (RRT).…”
Section: Methodsmentioning
confidence: 99%
“…The Salford Kidney Study (SKS), is a longitudinal, prospectively collected, ongoing observational study with full ethical permission that has recruited and followed-up patients with non-dialysis dependent CKD (NDD-CKD) in the United Kingdom since March 2002 [ 25 , 28 ]. This large NDD-CKD cohort consists of > 3500 patients that have provided their informed consent when admitted to the nephrology inpatient centre at Salford Royal Hospital or referred to nephrology outpatient clinics [ 8 , 26 ]. The participants in the current study were ≥ 18 years at the time of consent with (eGFR) < 60 ml/min/1.73 m 2 who had not started renal replacement therapy (RRT).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, our inclusion criteria focused solely on patients with linear progression within the rapid progression group. Non-linear decline is common, yet these patients often tend to have different phenotypes and outcomes, and as of yet the proteomic signature of this cohort has not been studied specifically [ 38 ]. Additionally, while we carried out internal validation of our findings, and data were analysed using fold-change analysis (which is not affected by overfitting), it is important to acknowledge that machine learning models developed in this study require further validation in independent external samples to demonstrate robustness and generalisability of the results, for clinical utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we also found that higher eGFR was a protective factor among CKD patients. Previous work shows that the lower eGFR, the higher the risk of CKD progression and incident ESKD among those with CKD [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%